Enhanced Antibacterial Potential of Amoxicillin against Helicobacter pylori Mediated by Lactobionic Acid Coated Zn-MOFs - Haseena; Adnan Khan; Fariha Aslam; Tasmina Kanwal; Muhammad Raza Shah; Atif Ali Khan Khalil; Syed Wadood Ali Shah; Eida M. Alshammari; Eman A. El-Masry; Gaber El-Saber Batiha; Roua S. Baty (MDPI AG, 2021)
H. pylori (Helicobacter pylori) causes a common chronic infectious disease and infects around 4.4 billion people worldwide. H. pylori was classified as a member of the primary class of stomach cancer (stomach adenocarcinoma). Hence, this study was conducted to design a novel lactobionic acid (LBA)-coated Zn-MOFs to enhance bactericidal activity of Amoxicillin (AMX) against H. pylori. The synthesized Zn-MOFs were characterized by various techniques which included Dynamic Light Scattering (DLS), Fourier Transform Infrared (FT-IR) Spectroscopy, Powder X-ray diffraction, scanning electron microscope, and atomic force microscope. They were capable of encapsulating an increased amount of AMX and investigated for their efficacy to enhance the antibacterial potential of their loaded drug candidate. Interestingly, it was found that LBA-coated Zn-MOFs significantly reduced the IC50, MIC, and MBIC values of AMX against H. pylori. Morphological investigation of treated bacterial cells further authenticated the above results as LBA-coated Zn-MOFs-treated cells underwent complete distortion compared with non-coated AMX loaded Zn-MOFs. Based on the results of the study, it can be suggested that LBA-coated Zn-MOFs may be an effective alternate candidate to provide new perspective for the treatment of H. pylori infections.